Preparation of MCM-41 silica using the cationic surfactant blend. - Thommes, Matthias; et al. (Adsorption-Journal of the International Adsorption Society, 2007)
A series of samples of MCM-41 silica was synthesized using surfactant blends of 1-alkyl-3-methylimidazolium and alkyltrimethylammonium salts or blends of two different 1-alkyl-3-methylimidazolium salts (alkyl denotes octyl or hexadecyl) as structure-directing agents. The pptn. of solid particles from a homogeneous water soln. of sodium metasilicate and surfactant blend was achieved by lowering the pH due to the hydrolysis of Et acetate added. The mol. sieves were characterized by scanning as well as transmission electron microscopy, X-ray powder diffraction, and nitrogen adsorption using a proper nonlocal d. functional theory approach for calcns. of the textural parameters. All the prepd. silicas were of MCM-41-type; they differ in the integral breadth of the pore size distribution curve and the presence of secondary mesopores. The best quality MCM-41 silica of spherical particle morphol. was synthesized by using of optimized blend of hexadecyltrimethylammonium bromide and 1-methyl-3-octylimidazolium chloride. The results obtained showed that spherical particles are composed of domains of perfectly ordered hexagonal porous structure. Some samples prepd. by using 1-alkyl-3-methylimidazolium salts featured a narrow pore size distribution. However, they contained a small vol. of secondary mesopores. [on SciFinder(R)]
Keywords: MCM41 silica prepn cationic surfactant